2004
DOI: 10.1177/10598405040200020601
|View full text |Cite
|
Sign up to set email alerts
|

A Study of School Nurse Job Satisfaction

Abstract: This study explored job satisfaction and changes needed to help boost levels of job satisfaction. Self-reported job satisfaction data were collected from 71 school nurses employed in elementary, middle, and high school settings via interactive focus groups. The subjects participated in a 30- to 45-minute focus group session that was audiotaped and transcribed by the principal investigator. Beliefs about job satisfaction were identified and classified into exclusive categories or themes. While the majority of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 8 publications
3
18
0
1
Order By: Relevance
“…Another area of dissatisfaction amongst nurses reported in the literature is remuneration (Campbell et al, 2004; Curtis & Glacken, 2014; Delobelle et al, 2011; Halcomb et al, 2018; Junious et al, 2004). Our study found that respondents were least satisfied with the factor “pay,” indicating that they did not feel that they were paid fairly for the work they do and are not satisfied with the salary they receive.…”
Section: Discussionmentioning
confidence: 99%
“…Another area of dissatisfaction amongst nurses reported in the literature is remuneration (Campbell et al, 2004; Curtis & Glacken, 2014; Delobelle et al, 2011; Halcomb et al, 2018; Junious et al, 2004). Our study found that respondents were least satisfied with the factor “pay,” indicating that they did not feel that they were paid fairly for the work they do and are not satisfied with the salary they receive.…”
Section: Discussionmentioning
confidence: 99%
“…The studies of other researchers point to very similar problems. According to Junious et al (23), school nurses in the Unites States are usually content with their job, but complain about low salary.…”
Section: Discussionmentioning
confidence: 99%
“…WHO pays much attention to the issues of medical personnel provision of health care system 1 . WHO notes that the effectiveness of health care systems operation depends on their being provided with highly qualified medical personnel 2 .…”
Section: Introductionmentioning
confidence: 99%